Religious Moderation in the Bakar Batu Tradition At the Dani Muslim Community in Jayawijaya, Papua Province, Indonesia - Athoillah Islamy; Ahmad Syarif Makatita (The Pontianak State Institute of Islamic Studies, 2022)
This qualitative study aims to identify religious moderation in the Bakar Batu tradition for the Dani Muslim community in Jayawijaya, Papua Province. The indicator of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia becomes the analytical theory in this study. Data collection techniques through observation, interviews and documentation. The nature of this research approach is descriptive-analytic. Meanwhile, data analysis techniques go through three stages, namely data reduction, data presentation, and data verification. The results show that there is a dimension of mainstreaming religious moderation in the practice of the Bakar Batu tradition by the Dani Muslim community in Jayawijaya. First. dimensions of the value of tolerance in realizing harmony between religious people. This is realized through the creation of two holes for dishes. One hole is for food for Muslims, and the other is for food for non-Muslims. Thus the Bakar Batu tradition can still run with the nuances of full harmony between religious people. Second, the dimension of accommodative value to local culture in harmonizing religious teachings and local traditions. This is realized by replacing pork which is the main dish in the Bakar Batu tradition with halal meat. Thus, the Bakat Batu tradition can still be preserved by the Dani Muslim community without having to deviate from the normative provisions of Islamic teachings. The theoretical implication of this research shows that the mainstreaming of religious moderation by the Ministry of Religion of the Republic of Indonesia can be a paradigmatic basis as well as an approach in realizing harmonious relations between Islamic teachings and local cultural pluralism in Indonesia. The limitation of this research is that it has not examined the form of the government's concrete role or strategy regarding the mainstreaming of religious moderation values in the Bakar Batu tradition and other traditions in Jayawijaya